Shifts in soil microorganisms in response to warming are consistent across a range of Antarctic environments - Yergeau, E.; Bokhorst, S.F.; Kang, S.; Jizhong, Z.; Greer, C.W.; Aerts, R.; Kowalchuk, G.A. (The ISME Journal, 2012)
Because of severe abiotic limitations, Antarctic soils represent simplified systems, where microorganisms are the principal drivers of nutrient cycling. This relative simplicity makes these ecosystems particularly vulnerable to perturbations, like global warming, and the Antarctic Peninsula is among the most rapidly warming regions on the planet. However, the consequences of the ongoing warming of Antarctica on microorganisms and the processes they mediate are unknown. Here, using 16S rRNA gene pyrosequencing and qPCR, we report highly consistent responses in microbial communities across disparate sub-Antarctic and Antarctic environments in response to 3 years of experimental field warming (+0.5 to 2°C). Specifically, we found significant increases in the abundance of fungi and bacteria and in the Alphaproteobacteria-to-Acidobacteria ratio, which could result in an increase in soil respiration. Furthermore, shifts toward generalist bacterial communities following warming weakened the linkage between the bacterial taxonomic and functional richness. GeoChip microarray analyses also revealed significant warming effects on functional communities, specifically in the N-cycling microorganisms. Our results demonstrate that soil microorganisms across a range of sub-Antarctic and Antarctic environments can respond consistently and rapidly to increasing temperatures. © 2012 International Society for Microbial Ecology All rights reserved.